Safety Engineering 2015
DOI: 10.7562/se2015.5.01.03
|View full text |Cite
|
Sign up to set email alerts
|

The Fire Simulation as a Safety Advantage in Fire Prediction and Fire Protection

Abstract: Fire presents the process of uncontrolled combustion that makes material damage and endangers human lives. It is important to know many factors that fire depends on for successful design and realization of fire protection systems. One of the most effective, the most economic and the most reliable ways to determine propagation of potential fire is the use of simulation programmes. In this paper, the usage of the PyroSim 2012 simulator in the potential fire de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…The detectors selection with their arrangement always must provide right time reaction and fire detection with acceptable price. These examples showed that increasing of detectors number doesn't bring great time reduction in sense of detection [12]. This research could be continued in several aspects, such as simulation with arrangement of fire detectors according to some typical way (triangle, hexagonal) or simulation of no typical objects with special content inside (for example, objects with different kind of roof with curvatures in theirs form and similar).…”
Section: Resultsmentioning
confidence: 92%
“…The detectors selection with their arrangement always must provide right time reaction and fire detection with acceptable price. These examples showed that increasing of detectors number doesn't bring great time reduction in sense of detection [12]. This research could be continued in several aspects, such as simulation with arrangement of fire detectors according to some typical way (triangle, hexagonal) or simulation of no typical objects with special content inside (for example, objects with different kind of roof with curvatures in theirs form and similar).…”
Section: Resultsmentioning
confidence: 92%
“…Of course, other arrangement of heat and smoke detectors was possible but it is important to note the fact that bigger number of detectors bring small benefit in sense of detection but significantly increase the price. Generally, simulation results enable to determinate all potential directions of the fire, smoke and flame propagation, to note and eliminate errors made in the object`s fire protection system design and realization, what is , in real situations, very often uneconomic and hard for realization [13]. Very important benefits that could be gained by simulation are the prediction of the potential evacuation routes and complete time needed for evacuation of all occupants inside some particular object, which is of the crucial importance according to the human safety, especially in the objects with lot of humans inside, such as schools, sanitary objects, residential objects, nurseries etc.…”
Section: Resultsmentioning
confidence: 99%
“…The second condition purports presence of appropriate flame detector, in combination with line-type heat detector. One such example of the multistory parking garage with line heat detectors in combination with flame detectors is presented on figure 4 [9,10,11,14,12].…”
Section: Linear Smoke Detectors-work Principlementioning
confidence: 99%